Measurement of the B+ Production Cross Section in pp Collisions at root s=7 TeV - Khachatryan, V. (2011)
Measurements of the total and differential cross sections d sigma/dp(T)(B) and d sigma/dy(B) for B+ mesons produced in pp collisions at root s = 7 TeV are presented. The data correspond to an integrated luminosity of 5.8 pb(-1) collected by the CMS experiment operating at the LHC. The exclusive decay B+ -> J/psi K+, with J/psi -> mu(+)mu(-), is used to detect B+ mesons and to measure the production cross section as a function of p(T)(B) and y(B). The total cross section for p(T)(B) > 5 GeV and vertical bar y(B)vertical bar < 2.4 is measured to be 28.1 +/- 2.4 +/- 2.0 +/- 3.1 mu b, where the first uncertainty is statistical, the second is systematic, and the last is from the luminosity measurement.